Analisis Sejarah Betawi dan Manajemen Risiko pada “Soto Betawi Susu Cianjur” - Indira Dandy, Dava (Jurnal Serambi Ekonomi dan Bisnis, 2024)
This study aims to trace the history of the development of Soto Betawi, identify and analyze the management set by “Soto Betawi Susu Cianjur” in marketing Soto Betawi in the modern era. Soto Betawi, a Betawi coconut milk soup dish, has become an integral part of Jakarta's culinary identity. This study found that Soto Betawi is not just food, but also presents the identity and spirit of the Betawi community.